PMO-107 Role of ERCP in the management of acute gallstone pancreatitis—a review of current practice. (28th May 2012) - Johnstone, M; Marriott, P; Royle, J; Hepburn, E; Torrance, A; Richardson, C; Patel, A; Bartlett, D; Pinkney, T
Abstract : Introduction: Cholecystectomy is the preferred definitive treatment to prevent further episodes of gallstone pancreatitis, if patients have clear bile ducts and are suitable for surgery. Endoscopic retrograde cholangio-pancreatography (ERCP) is utilised to either clear the biliary tree of gallstones prior to operation or as definitive treatment in those deemed unsuitable for surgery. We aimed to determine how ERCP is being utilised, its effect on recurrent pancreatitis and readmission rates. Methods: A multi-centre retrospective review was performed of patients presenting with their first episode of gallstone pancreatitis between 2006 and 2008. All patients with confirmed biochemical diagnosis of pancreatitis plus a radiological diagnosis of gallstones were included. Data were collected on demographics, ERCP, operative management and readmissions. Groups were compared using χ 2 and medians using Mann–Whitney U. Results: 523 patients were identified (36% male, median age 63) in seven acute hospital trusts. 166 (32%) underwent ERCP with 20 (13%) having a failed procedure. 127 (77%) underwent sphincterotomy with the common bile duct being clear in 80% (133). 28 (17%) were performed within 72 h of admission and 105 (63%) were performed during the index admission. There was no effect on the timing of ERCP in the likelihood of the procedure failing to be completed (median time 10 vs 10.5 days). 364 patients underwent cholecystectomy with 29% undergoing ERCP prior to surgery. ERCP was performed as the definitive procedure in 58 patients; median age 80 years compared to 58 years in those undergoing cholecystectomy (p two patients died following successful ERCPs; one 87 year old of Clostridium difficile colitis and one 81 year old of pancreatitis. There was one episode of post ERCP pancreatitis, and one bleed that resolved spontaneously. An additional 5 patients developed a second episode of pancreatitis subsequent to their ERCP. Sphincterotomy had not been performed in three of these cases (p=0.08). ERCP with the index admission was the only significant factor to reduce recurrent pancreatitis rates (OR 0.092 (0.013–0.673); p<0.01) however it failed to reduce the risk of readmission (OR 0.704 (0.39–1.26); P=0.24), which was only achieved by cholecystectomy within the index admission (OR 0.06 (0.01–0.4700); p<0.01). Conclusion: ERCP is currently being used as definitive treatment for gallstone pancreatitis in selected elderly patients. In our series ERCP had an acceptable rate of morbidity associated with the procedure, and was shown to significantly reduce the rate of recurrent pancreatitis. However, overall readmission rates were not improved by ERCP, with this only being achieved by cholecystectomy during the index admission. Competing interests: None declared.